Konstruksi Makna Sekolah Islam bagi Orang Tua Siswa - Filda Fatimah Tuzzahrah; Kokom Komariah; Anwar Sani (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2016)
The presence of Islamic schools is a revolutionary of the outmoded of Islamic education system to elite and prestigious institutions. Initially, the Islamic school was formed in an effort to create intelligent students who also have a religious character. However, the trend of Islamic schools is growing rapidly along with economic progress of society. The overhauled system that offers many advantages apparently succeeded in making high demand of Islamic schools. Although the price offered is fantastic, the public interest is so high to this model by building positive image and reputation. This study reveals the meaning, motives and experiences of parents in the Internatonal Islamic Schools Jakarta. The method used is qualitative with phenomenology type of study. The result that Islamic school was interpreted by student parents as positive view. Their motives to chosse the Islamic school because Islamic schools could balance between live now and hereafter.